2021
DOI: 10.1007/s10566-021-09655-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Anxiety of Adolescents in Québec

Abstract: Background Several studies conducted since the beginning of the COVID-19 pandemic have shown its harmful effects on young people’s mental health. In Québec and Canada, few studies have focussed on adolescents, and even fewer of these studies have examined this subject using a methodology that involved comparisons of data obtained before and during the pandemic, which is the purpose of this study. Objective The objective of this study is to determine the impact of the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
2
24
0
2
Order By: Relevance
“…In sum, the results of this follow‐up study seem to be less situational and may reflect potential chronic effects of the COVID‐19 pandemic on adolescents' academic motivation. The findings are in line with several recent studies indicating that youth experienced a decrease in motivation toward schoolwork 10,11 as well as high levels of distress during the COVID‐19 pandemic 12‐18 . Consequently, it is likely that they had difficulties engaging in activities that, in normal circumstances, were salient to them.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In sum, the results of this follow‐up study seem to be less situational and may reflect potential chronic effects of the COVID‐19 pandemic on adolescents' academic motivation. The findings are in line with several recent studies indicating that youth experienced a decrease in motivation toward schoolwork 10,11 as well as high levels of distress during the COVID‐19 pandemic 12‐18 . Consequently, it is likely that they had difficulties engaging in activities that, in normal circumstances, were salient to them.…”
Section: Discussionsupporting
confidence: 90%
“…That being said, and as highlighted by Klootwijk et al, 10 it is difficult to determine whether such motivational changes are due to the COVID‐19 pandemic, especially since students' motivation tends to decline within a school year and across grade levels 1‐4 . However, as we already pointed out, several recent studies revealed that adolescents' mental health has been negatively impacted by the COVID‐19 pandemic 12‐18 and our findings leave to think that their motivational resources were also impacted.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The majority of studies to date are either cross-sectional or involve online convenience samples that demonstrate change in mental health and well-being during the course of the pandemic [ 9 , 14 ]. Studies have also used historical data to predict mental health outcomes during the pandemic [ 15 ] as well as independent samples to provide pre-pandemic comparisons [ 16 ]. Although these studies have provided valuable early insights, the convenience and non-probability samples are likely to contain substantial bias [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is di cult to determine whether these changes are due to the pandemic, especially since motivation tends to decline as students progress through grades (Fredricks & Eccles, 2002;Jacobs et al, 2002;Paulick et al, 2013;Watt, 2004). However, as we already pointed out, several recent studies revealed that students' mental health has been negatively impacted by this pandemic (Guimond et al, 2021;Lane et al, 2021;Rogers et al, 2021;Rothe et al, 2021;Tang et al, 2021;Tardif-Grenier et al, 2021;Vaillancourt et al, 2021) and these ndings leave to think that their motivational resources were also negatively impacted.…”
Section: Discussionmentioning
confidence: 92%